Engineered Human Nanoferritin Bearing the Drug Genz-644282 for Cancer Therapy - Elisabetta Falvo; Alessandro Arcovito; Giamaica Conti; Giuseppe Cipolla; Martina Pitea; Veronica Morea; Verena Damiani; Gianluca Sala; Giulio Fracasso; Pierpaolo Ceci (MDPI AG, 2020)
Gastrointestinal tumors, including pancreatic and colorectal cancers, represent one of the greatest public health issues worldwide, leading to a million global deaths. Recent research demonstrated that the human heavy chain ferritin (HFt) can encapsulate different types of drugs in its cavity and can bind to its receptor, CD71, in several solid and hematological tumors, thus highlighting the potential use of ferritin for tumor-targeting therapies. Here, we describe the development and characterization of a novel nanomedicine based on the HFt that is named The-0504. In particular, this novel system is a nano-assembly comprising an engineered version of HFt that entraps about 80 molecules of a potent, wide-spectrum, non-camptothecin topoisomerase I inhibitor (Genz-644282). The-0504 can be produced by a standardized pre-industrial process as a pure and homogeneously formulated product with favourable lyophilization properties. The preliminary anticancer activity was evaluated in cultured cancer cells and in a mouse model of pancreatic cancer. Overall results reported here make The-0504 a candidate for further preclinical development against CD-71 expressing deadly tumors.